tidal breathing model for the multiple inert gas elimination technique - Whiteley, J; Gavaghan, D; Hahn, C (1999)
The tidal breathing lung model described for the sine-wave technique (D. J. Gavaghan and C. E. W. Hahn. Respir. Physiol. 106: 209-221, 1996) is generalized to continuous ventilation-perfusion and ventilation-volume distributions. This tidal breathing model is then applied to the multiple inert gas elimination technique (P. D. Wagner, H. A. Saltzman, and J. B. West. J. Appl. Physiol. 36: 588-599, 1974). The conservation of mass equations are solved, and it is shown that 1) retentions vary considerably over the course of a breath, 2) the retentions are dependent on alveolar volume, and 3) the retentions depend only weakly on the width of the ventilation-volume distribution. Simulated experimental data with a